Putting the French Duty of Vigilance Law in context: towards corporate accountability for human rights violations in the Global South? - Schilling-Vacaflor, Almut (Human rights review, 2021)
The adoption of the French Duty of Vigilance law has been celebrated as a milestone for advancing the transnational business and human rights regime. The law can contribute to harden corporate accountability by challenging the “separation principle” of transnational companies and by obligating companies to report on their duty of vigilance. However, the question of whether the law actually contributes to human rights and environmental protection along global supply chains requires empirically grounded research that connects processes in home and host state countries. This paper contributes to such a new research agenda by linking political ecology literature and empirical insights from the Global South to research on due diligence regulations. With reference to field research data on contestations between the oil and gas company Total E&P and indigenous communities in Bolivia, I argue that the burden of proof and contestations over valid knowledge represent major obstacles when trying to establish legal liability.